Recollections - Neurath, Eva Urvasi 1908-1999 (Thames & Hudson, 2016)
Eva Neurath, co-founder of Thames & Hudson, wrote this memoir for her granddaughters, and it is a private story of a remarkable 20th-century-life. She was born in Berlin and grew up there in the Twenties, when anything was possible. But this was a world in the grip of a traumatic change. Pursued by the Gestapo, Eva and her family left Berlin in 1938, first for Rotterdam, then London. She was offered a job at Adprint by Walter Neurath where she worked before they founded a new publishing house together, Thames & Hudson, in 1949. Her life and marriage with Walter moved in circles of art, archeology and history. The memoir ends in 1981, but Eva's work continued until 1999, the year she died, and the story is filled out by her son, Stephan Feuchtwang